2016
DOI: 10.5194/amt-9-4079-2016
|View full text |Cite
|
Sign up to set email alerts
|

Proposed standardized definitions for vertical resolution and uncertainty in the NDACC lidar ozone and temperature algorithms – Part 3: Temperature uncertainty budget

Abstract: Abstract.A standardized approach for the definition, propagation, and reporting of uncertainty in the temperature lidar data products contributing to the Network for the Detection for Atmospheric Composition Change (NDACC) database is proposed. One important aspect of the proposed approach is the ability to propagate all independent uncertainty components in parallel through the data processing chain. The individual uncertainty components are then combined together at the very last stage of processing to form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 47 publications
(55 reference statements)
2
36
0
Order By: Relevance
“…Temperature uncertainty ranges from 0.5 K in the mid-stratosphere to 2 K in the lower mesosphere, and more than 10 K in the upper mesosphere as a result of lower signal-to-noise ratios and uncertainty owing to the "a priori" temperature initialization. A full uncertainty budget for Rayleigh/Raman temperature lidars with a specific example for the Mauna Loa system is presented in Leblanc et al (2016b). At Réunion, the Rayleigh lidar system was established at the Saint-Denis campus (approximately sea level) by the Laboratoire de l'Atmosphere et des Cyclones (LACy) and was operational from 1994 to 2009.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature uncertainty ranges from 0.5 K in the mid-stratosphere to 2 K in the lower mesosphere, and more than 10 K in the upper mesosphere as a result of lower signal-to-noise ratios and uncertainty owing to the "a priori" temperature initialization. A full uncertainty budget for Rayleigh/Raman temperature lidars with a specific example for the Mauna Loa system is presented in Leblanc et al (2016b). At Réunion, the Rayleigh lidar system was established at the Saint-Denis campus (approximately sea level) by the Laboratoire de l'Atmosphere et des Cyclones (LACy) and was operational from 1994 to 2009.…”
mentioning
confidence: 99%
“…The signals collected by the photomultipliers are sampled by multi-channel scalers (MCS) at 2 µs intervals (300 m) and saved in the raw data files every 5 to 20 min, depending on the period considered over the 1993-present time series. During processing, the temperature profiles are further integrated to a 2 h average and then vertically smoothed to yield an effective resolution ranging from 300 m in lower stratosphere to 4 km in the upper mesosphere, following the NDACC-standardized definition detailed in Leblanc et al (2016a). Temperature uncertainty ranges from 0.5 K in the mid-stratosphere to 2 K in the lower mesosphere, and more than 10 K in the upper mesosphere as a result of lower signal-to-noise ratios and uncertainty owing to the "a priori" temperature initialization.…”
mentioning
confidence: 99%
“…It is almost less than 3000 m below the 0.9 cutoff 5 height, however, it increases rapidly to 5000 m around the 0.8 cutoff line. Leblanc et al (2016b) recommended two standardized definitions for a temperature profile vertical resolution. In order to compare the retrieved temperature profiles using the OEM and the HC method, the two vertical resolution definitions given by Leblanc et al (2016b) were used to find the best bin size for the HC method so it would have an identical vertical resolution to the OEM retrieval.…”
Section: Uncertainty Budget For the Pcl Climatologymentioning
confidence: 99%
“…Leblanc et al (2016b) recommended two standardized definitions for a temperature profile vertical resolution. In order to compare the retrieved temperature profiles using the OEM and the HC method, the two vertical resolution definitions given by Leblanc et al (2016b) were used to find the best bin size for the HC method so it would have an identical vertical resolution to the OEM retrieval. We found that 264 m co-added bins and a 3's and 5's filter gave a vertical resolution of 1008 m, close to the OEM temperature retrieval grid (1056 m).…”
Section: Uncertainty Budget For the Pcl Climatologymentioning
confidence: 99%
See 1 more Smart Citation